2021
DOI: 10.3917/sta.pr1.0027
|View full text |Cite
|
Sign up to set email alerts
|

Effet d’une routine centrée sur l’imagerie mentale et sur l’efficacité du service chez des joueurs de tennis experts

Abstract: Cette étude expérimentale porte sur les effets d’une routine de préparation au service composée principalement d’imagerie mentale (IM) selon une modalité visuelle externe centrée sur la trajectoire de la balle et la zone cible à atteindre. Quarante joueurs experts étaient aléatoirement séparés en deux groupes expérimentaux : contrôle et imagerie. Ils ont réalisé un pré-test (i.e., 25 premières balles de service en condition de match), 20 séances d’acquisition (i.e., pratique physique + IM ou pratique physique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Indeed, while beneficial effects have been observed in children (e.g., Atienza et al, 1998), teens (e.g., Dana and Gozalzadeh, 2017) or adults (Cherappurath and Elayaraja, 2017) playing at a recreational level, others studies showed a positive effect of MI in teen with a regional level (Guillot et al, 2012), in young adults at collegiate level (Daw and Burton, 1994), in youth (Dohme et al, 2020) or young adult (Robin et al, 2007) elite players and even at a professional level (Mathers, 2017). More specifically, our results confirm the beneficial effect of MI on service performance in teen (Guillot et al, 2013;Türk et al, 2019) and young adults (e.g., Fekih et al, 2020;Dominique et al, 2021) skilled (i.e., national and elite) and international (e.g., Mathers, 2017) tennis players. However, the results of the current study did not show any improvement in service speed.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Indeed, while beneficial effects have been observed in children (e.g., Atienza et al, 1998), teens (e.g., Dana and Gozalzadeh, 2017) or adults (Cherappurath and Elayaraja, 2017) playing at a recreational level, others studies showed a positive effect of MI in teen with a regional level (Guillot et al, 2012), in young adults at collegiate level (Daw and Burton, 1994), in youth (Dohme et al, 2020) or young adult (Robin et al, 2007) elite players and even at a professional level (Mathers, 2017). More specifically, our results confirm the beneficial effect of MI on service performance in teen (Guillot et al, 2013;Türk et al, 2019) and young adults (e.g., Fekih et al, 2020;Dominique et al, 2021) skilled (i.e., national and elite) and international (e.g., Mathers, 2017) tennis players. However, the results of the current study did not show any improvement in service speed.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies showed, in tennis, the beneficial effects of using MI (e.g., de Sousa Fortes et al, 2019;Dominique et al, 2021) or self-talk (e.g., Zourbanos et al, 2015) on service performance and successful game outcome; and other studies supported the combination of these two mental techniques, among others, in mental skills training program (e.g., Dohme et al, 2020). That's why, this original study aimed to evaluate, in skilled tennis players, the influence of a combination of MI (based on the trajectory and the target to be reached) and controlled motivational self-talk, performed before the actual strike, on the performance of the first service balls in match play situations, which could be especially beneficial as it is the only shot that is not preceded by another leaving the server enough time to perform it.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations